Knowledge management, organizational commitment and knowledge-worker performance: The neglected role of knowledge management in the public sector. Issue 5 (2nd September 2019) - Razzaq, Shahid; Shujahat, Muhammad; Hussain, Saddam; Nawaz, Faisal; Wang, Minhong; Ali, Murad; Tehseen, Shehnaz
Abstract : Purpose: Knowledge management in the public sector is relatively an ignored avenue of research and practice that has recently been given attention. Knowledge management initiatives in the public sector are now not limited to the developed countries anymore. The public sectors of various developing countries including Pakistan have developed knowledge management functions to address the problems of low organizational commitment (higher turnover rates) and knowledge-workers' performance. Consequently, the purpose of this paper is to examine the mediation role of organizational commitment in the relationship between knowledge management practices and knowledge-worker performance. Design/methodology/approach: The data were gathered from 341 knowledge workers of the public sector health department of Punjab Province, Pakistan, where knowledge management unit initiative has been taken. It was then analyzed using the structural equation modeling. Findings: Organizational commitment partially mediates the relationship between knowledge management practices and knowledge-work performance. Practical implications: The public sector policy makers are strongly advised to implement knowledge management units and practices in order to enhance knowledge-work performance as well as organizational commitment. Originality/value: First, the model on the mediating role of organizational commitment has never been examined before. Second, the data collection from the public Health Department of Pakistan, a developing country, is relatively rare because the public sector knowledge management studies have mostly been conducted in developed countries. Finally, this study extends the literature on knowledge management in the public sector that is the developing theme in knowledge management discipline while adding knowledge management as a toolkit to enhance knowledge-workers', organizational commitment and knowledge-work performance.